Evaluation of the Expression of Immunohistochemical Staining of PDL1 in Renal Cell Cancer - Rihab Mohammed Edress Al-Nuaimy; Nadwa SM. Al-Azzo (University of Mosul, 2024)
Background and objectives: To evade anti-tumour responses, tumour cells expressed programmed death ligand 1 (PDL1), which play a role in suppressing the adaptive arm of immune systems. It has been disputed, meanwhile, whether PDL1 expression in Renal cell cancer (RCC) has any predictive value. Anti-PDL1 can decrease tumour size, inhibit immunological checkpoints, and improve overall RCC survival. In our study, our primary objective was to evaluate the statement of PDL1 immunostain in RCC. Methods: Fifty samples of primary RCC were used in a prospective and retrospective case series research. From Formalin-fixed and paraffin-embedded (FFPE) blocks, hematoxylin and eosin (H and E) stained glass slides were prepared, and the diagnosis was updated. PDL1 immunohistochemical stain (PDL1 IHC) was conducted for all cases, using the EnVision FLEX visualization system on Autostainer Link 48 with PDL1 IHC 22C3 pharmDx (Dako) monoclonal mouse anti-PDL1. Results: PDL1 is found to be expressed in (56 %). The mean age of patients was (54.8±13.52) years, most of them were in their 50s and 60s year old, with male to female ratio of 1.94:1. Clear cell RCC consists of (78%), and most common in stage 1 and stage 3 with statistically significant p–value. Clear cell carcinoma was statistically significant with stage 1 and 3 and grade 2 was the most frequent. The majority of instances of clear cell RCC were on the left side. Conclusion: PDL1 provide an excellent template for confirming the diagnosis of RCC.